THE COMMUNITY OF SOIL YEASTS IN GUNUNG HALIMUN NATIONAL PARK - Atit Kanti; I Made Sudiana; Heddy Julistiono (BERITA BIOLOGI, 2001)
Fifty-two isolates were isolated from Gunung Halimun National Park on the basis of morphological and some physiological characteristics.Those isolates were belonged to three groups namely, ascomycetous, basidiomycetous and imperfect yeasts.Rhodotolum sp.was only found in Ciptarasa site at 1500 m asl, ascomycetous yeasts was only isolated from deteoretic root in Gunung Botol site, while Candida sp.(small globose shaped cells) was only isolated from soil at 1800 m asl of Gunung Botol site. Type of plant species appeared has no effect on yeasts diversity as shown by similar yeasts diversity was observed at rhizosphere soil of three dominating plant (Schima waallichii, Castanopsis javanica and Altingia excelsa) at Cikaniki study site.